THE ROLE OF CULTURAL HEGEMONY IN MARIPOSA IN MAINTAINING GENDER COLOR ASSUMPTION - Nur Nabilah Fauziyah (International Journal of Humanity Studies (IJHS), 2020)
The development of technology has a big contribution to creating cultural phenomena of global citizens. A movie as part of cultural products in this matter is not only considered as a cultural phenomenon, but it also can takes a significant role in shaping the culture itself. Specifically, this paper was conducted to discover denotative and connotative meaning of pink and blue color of school uniform in Mariposa and its relation of practicing hegemony in the context of gender color. In analyzing the meaning of color use in school uniform and the relation between pink and blue uniform with hegemony, the author uses Barthes semiotic and Gramscis hegemony as the theory. The data were collected from the images of movie scenes in Mariposa when the characters wear their school uniform. After analyzing the data, this study found that (1) The use of pink and blue color as a color of school uniform in Mariposa represents masculinity and feminity, (2) Mariposa movie is considered as a medium in operating hegemony, and (3) The hegemony is represented through pink and blue color of the movie characters uniform.